1994
DOI: 10.1073/pnas.91.1.167
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor-receptor mutant lacking the autophosphorylation sites induces phosphorylation of Shc protein and Shc-Grb2/ASH association and retains mitogenic activity.

Abstract: Epidermal growth factor (EGF) receptor (EGFR) can induce cell growth and transformation in a ligand-dependent manner. To examine whether the autophosphorylation of EGFR correlates with the capacity of the activated EGFR to induce cell growth and transformation, we truncated the human EGFR just after residue 1011, removing all three major autophosphorylation sites (DEL1011). Further, a point mutation was introduced at another autophosphorylation site, Tyr-992 -* Phe (DEL1011+F992). The wild-type and mutant rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
87
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 26 publications
8
87
1
Order By: Relevance
“…We also observed a similar age-related decrease in the association of the EGF receptor with the SH2 domain of the Shc protein, which recognizes tyrosine 1173, although the magnitude of the association was not as great as with the Shc-PTB domain (data not shown). The idea that reduced association of Shc with the EGF receptor due to defects in autophosphorylation sites with the effect of reducing mitogenic activity is supported by the data of Gotoh et al (42). A cell line containing a deletion mutant of the EGF receptor that lacked the autophosphorylation sites downstream of residue 1011 was used to show that EGF treatment could still result in stimulation of Shc phosphorylation but retained only approximately 20% of its mitogenic activity when measured as cell growth.…”
Section: Discussionsupporting
confidence: 52%
“…We also observed a similar age-related decrease in the association of the EGF receptor with the SH2 domain of the Shc protein, which recognizes tyrosine 1173, although the magnitude of the association was not as great as with the Shc-PTB domain (data not shown). The idea that reduced association of Shc with the EGF receptor due to defects in autophosphorylation sites with the effect of reducing mitogenic activity is supported by the data of Gotoh et al (42). A cell line containing a deletion mutant of the EGF receptor that lacked the autophosphorylation sites downstream of residue 1011 was used to show that EGF treatment could still result in stimulation of Shc phosphorylation but retained only approximately 20% of its mitogenic activity when measured as cell growth.…”
Section: Discussionsupporting
confidence: 52%
“…It also suggests that the kinase domain of the activated EGF receptor may not be responsible for Shc phosphorylation on Tyr-317, since although being very weakly phosphorylated following EGF stimulation, the GST-SHCY239/240F forms a complex with the activated EGFR. Previous studies have reported that Shc can undergo tyrosine phosphorylation in the absence of specific binding sites on the EGFR (42,43) and that phosphorylation on Tyr-317 does not depend on Shc binding to the activated EGFR (44). In addition, it has been shown that in v-Src or v-Sea transformed cells, Shc is phosphorylated and associates with Grb2 (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Neither Tyr-1173 nor Tyr-992 fulfills either the SH2 or SAIN domain-binding criteria, and their mode of interaction is unclear, although our results showing that mutation of the Pro in the IR NPXY motif reduces but does not eliminate SHC interaction, suggests that Tyr-1173 (NAGY) may also serve as a less efficient SAIN domain-binding site. Two other studies have suggested that mutation or deletion of all phosphorylated tyrosines in the EGF receptor showed phosphorylation of SHC and unimpaired mitogenic signaling (14,46). The explanation for these different results is unclear.…”
Section: Discussionmentioning
confidence: 99%